1991
DOI: 10.1002/ar.1092300105
|View full text |Cite
|
Sign up to set email alerts
|

The subdural space interpreted as a cellular layer of meninges

Abstract: The subdural region within the cranial meninges is examined in guinea pigs by electron microscopy. The fine structures of the arachnoid membrane and dura are described separately in specimens that have been isolated from each other during removal from the cranial cavity. In addition, the fine structure of the intact dura-arachnoid is described, where the subdural space would be present in an undisrupted state. Lastly, the inner surface of the dura and the outer surface of the arachnoid membrane are examined at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The subdural space was reported to occur in a specific cell layer of flattened fibroblasts. Frederickson found that the number of cells varied with location and were consistent with the dural border cells described by Nabeshima et al 13 Haines described periosteal and meningeal dural layers. 17 Modified fibroblasts with no organized junctional complexes were seen beneath the meningeal layer.…”
Section: Subdural Hematoma Anatomysupporting
confidence: 81%
See 1 more Smart Citation
“…The subdural space was reported to occur in a specific cell layer of flattened fibroblasts. Frederickson found that the number of cells varied with location and were consistent with the dural border cells described by Nabeshima et al 13 Haines described periosteal and meningeal dural layers. 17 Modified fibroblasts with no organized junctional complexes were seen beneath the meningeal layer.…”
Section: Subdural Hematoma Anatomysupporting
confidence: 81%
“…39 Frederickson reported that separation of the dura and arachnoid was easily performed in a guinea pig model. 13 He found that before separation the dura and arachnoid were in contact and after separation the arachnoid's outer surface was irregular with cytoplasmic debris and disrupted cell membranes. The subdural space was reported to occur in a specific cell layer of flattened fibroblasts.…”
Section: Subdural Hematoma Anatomymentioning
confidence: 99%
“…There is no naturally occuring biological space at the dura-arachnoid juntion in the calvarial region (11). While the periosteal dura mater was attached tenaciously to the cranial base and includes more extracellular collagen, the meningeal dura mater has less extracellular collagen and the inner aspect, has a special cell layer known as the dural border cell (DBC) layer (8). The arachnoid membrane consists of two different cell layers; the arachnoid barrier cell (ABC) layer, and the arachnoid trabeculea (11).…”
Section: Discussionmentioning
confidence: 99%
“…Separation of the arachnoid mater from the meningeal dura (dura propria) occurred at the dural border cell layer that contains no collagen. 18,23 The meningeal dura was depicted as thinner than the periosteal dura. Allen and Didio 1 observed that, upon separation of the arachnoid from the meningeal dura, the dural border cells layer seldom remains intact as it forms the plane of separation.…”
Section: Dura Matermentioning
confidence: 99%